Lactic acid bacteria and bifidobacteria deliberately introduced into the agro-food chain do not significantly increase the antimicrobial resistance gene pool - Vita Rozman; Petra Mohar Lorbeg; Primož Treven; Tomaž Accetto; Majda Golob; Irena Zdovc; Bojana Bogovič Matijašić (Gut Microbes)
Lactic acid bacteria (LAB) and bifidobacteria may serve as reservoirs of antimicrobial resistance, but the risk posed by strains intentionally introduced into the agro-food chain has not yet been thoroughly investigated. The aim of our study was to evaluate whether probiotics, starter and protective cultures, and feed additives represent a risk to human health. In addition to commercial strains of LAB and bifidobacteria, isolates from human milk or colostrum, intestinal mucosa or feces, and fermented products were analyzed. Phenotypic susceptibility data of 474 strains showed that antimicrobial resistance was more common in intestinal isolates than in commercial strains. Antimicrobial resistance genes (ARGs) and mobile genetic elements (MGEs) were characterized in the whole genome sequences of 1114 strains using comparative genomics. Intrinsic ARGs were abundant in enterococci, bifidobacteria, and lactococci but were considered non-risky due to the absence of MGEs. The results revealed that 13.8% of commercial strains contained acquired ARGs, most frequently for tetracycline. We associated 75.5% of the acquired ARGs with known or novel MGEs, and their potential for transmission was assessed by examining metagenomic sequences. We confirmed that ARGs and MGEs were not as abundant or diverse in commercial strains as in human intestinal isolates or isolates from human milk, suggesting that strains intentionally introduced into the agro-food chain do not pose a significant threat. However, attention should be paid especially to individual probiotic strains containing elements that have been shown to have high potential for transferability in the gut microbiota.Abbreviations: ARG, antimicrobial resistance gene; ICE, integrative and conjugative element; IME, integrative and mobilizable element; LAB, lactic acid bacteria; MDR, multidrug resistance; MIC, minimum inhibitory concentration; MGE, mobile genetic element; TRRPP, tetracycline-resistant ribosomal protection protein; WGS, whole genome sequences